Bibliometrics and Citation Analysis of “BACA: Jurnal Dokumentasi dan Informasi” Published During 2015-2019 - Dwi Ridho Aulianto; Wahid Nashihuddin (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
This study aims to know deeply about BACA: Documentation and Information Journal published during 2015-2019. The aspects of the study are the distribution of articles, number of pages, authorship patterns, citation numbers, and form of visualization. This bibliometric research obtained data in http://jurnalbaca.pdii.lipi.go.id, which was then processed and analyzed using Ms. Excel, Publish or Perish (PoP) and VOSviewer application. The study showed that this journal has a frequency of publication 2 times a year (June and December) and has published 71 articles during 2015-2019, with 30 single authors (42.25%) and 41 collaborative authors (57.75). The number of writers who contributed during the period was 146 people both single and collaborative, and in 2019 there were 20 article titles with the largest number of authors 46 people (31.51%). Distribution of articles based on publication numbers during the period, namely issue 1 (June) published as many as 34 articles (47.89%) and issue 2 (December) published as many as 37 articles (52.11%) with a total of 975 pages with an average of 11-15 pages. This journal has 30 citations, an annual citation 6.00, a written citation 0.42, h-index 2, g-index 2, hI, norm 2, and hla 0.40. The strength of the network between the authors and the frequency of collaboration can be seen in VosViewer’s visualization.